The dilemma of neuroprotection trials in times of successful endovascular recanalization - Schmidt-Pogoda, Antje; Kaesmacher, Johannes; Bonberg, Nadine; Werring, Nils; Strecker, Jan-Kolja; Koecke, Mailin Hannah Marie; Beuker, Carolin; Gralla, Jan; Meier, Raphael; Wiendl, Heinz; Minnerup, Heike; Fischer, Urs; et al. (Frontiers in Neurology, 2024)
Background The “translational roadblock” between successful animal stroke studies and neutral clinical trials is usually attributed to conceptual weaknesses. However, we hypothesized that rodent studies cannot inform the human disease due to intrinsic pathophysiological differences between rodents and humans., i.e., differences in infarct evolution. Methods To verify our hypothesis, we employed a mixed study design and compared findings from meta-analyses of animal studies and a retrospective clinical cohort study. For animal data, we systematically searched pubmed to identify all rodent studies, in which stroke was induced by MCAO and at least two sequential MRI scans were performed for infarct volume assessment within the first two days. For clinical data, we included 107 consecutive stroke patients with large artery occlusion, who received MRI scans upon admission and one or two days later. Results Our preclinical meta-analyses included 50 studies with 676 animals. Untreated animals had a median post-reperfusion infarct volume growth of 74%. Neuroprotective treatments reduced this infarct volume growth to 23%. A retrospective clinical cohort study showed that stroke patients had a median infarct volume growth of only 2% after successful recanalization. Stroke patients with unsuccessful recanalization, by contrast, experienced a meaningful median infarct growth of 148%. Conclusion Our study shows that rodents have a significant post-reperfusion infarct growth, and that this post-reperfusion infarct growth is the target of neuroprotective treatments. Stroke patients with successful recanalization do not have such infarct growth and thus have no target for neuroprotection.